- ; Impact of non-agricultural businesses on rural employment in south Kazakhstan province - Saule Esengazieva (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
, , , , . , , « ». : , , . , , - (). , - , ( ) , , , . , , , . – – As a result of the on-going global economic crisis, issues of employment, unemployment and labor mobility in Kazakhstan are becoming increasingly important and remain central to the scientific, public, political and economic activities of relevant departments, organizations and enterprises. In order to protect citizens from unemployment during the crisis, the state developed what can be described as a "survival strategy". This strategy aims at implementing state programs for the creation of social work places, the training of specialists, and the organization of youth internships. The study is based on interviews with workers from akimats and agricultural departments, rural entrepreneurs, and representatives of non-agricultural business in the South Kazakhstan province (SKP). The main areas of non-agricultural business in rural areas of SKP are processing of agricultural raw materials and products, trading and procurement activities, public catering in rural settlements (roadside shops and cafes) and related services, construction of residential and industrial facilities, handcrafts, and transport services. Non-agricultural business development in rural areas will contribute to the diversification of rural economic activities, expansion of sources of local budget revenues, increased sustainability of rural development via greater employment and self-employment opportunities, as well as raising the living standards of the rural population.
urn:nbn:de:gbv:3:2-81480
Keywords: P41; J60; J68; 330; employment; non-agricultural business; rural area; strategy; state support; Beschäftigung; außerlandwirtschafliche Beschäftigung; ländlicher Raum; Strategie; staatliche Unterstützung